Exploring the news media and scientific conversations around water quality in a water-rich basin of the United States - Christenson, Catherine; Murphy, Jennifer; Ortiz, Jaqueline (Frontiers in Environmental Science, 2025)
Community concerns about water availability vary depending on local economic, regulatory, environmental, and ecological considerations. In water-rich basins, water quality is often the focus of community concerns. As such, understanding community priorities in the context of water quality is crucial for informing scientists working in water-rich basins. In this work, we compiled over 6,500 local news articles (public discourse) and 190 scientific abstracts (scientific discourse) related to water-quality issues in the water-rich Illinois River Basin (ILRB) published between 2018 and 2022. We applied a Structural Topic Model (STM) to identify key water-quality topics within both datasets and explore the variability of newspaper topics geographically across the basin. Prevalent topics in both the public (local news articles) and scientific (abstracts) discourses were agriculture, drinking water quality, PFAS (per- and polyfluoroalkyl substances), and river ecosystem/fish. Topics exclusive to public discourse included water infrastructure, community development, and public water supply, while the scientific discourse focused more heavily on a wider range of agricultural issues. Furthermore, the public discourse varied geographically across the basin. Some topics are correlated with land use or urban/rural divides within the basin, and the frequency of many topics clearly varied across state (political) boundaries. Understanding and quantifying public and scientific discourses related to water-quality are important for scientists and water managers working in the basin to improve communication of critical science to the public.